Snake Bite: Pattern and Prevalence in DHQ Hospital Barkhan Balochistan (Medical Forum Monthly, 2024)
Objective: To examine the frequency and pattern of snake bite in District Barkhan Balochistan and its surrounding areas in Pakistan.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the DHQ Hospital District Barkhan Baluchistan from 1st January 2010 to 31st December 2012.Materials and Methods: In this study total 811 patients of both genders were included during the study period. Patients detailed history including age, sex, socio-economic status and residency, types of snakes identified, site of bite and time of bite to hospital visit time duration was examined.Results: There were 492 (60.67%) males while rest 39.33% females, Mostly patients were ages 20 to 40 years. Most of the patients 96.92% of incidences prefer treatment from DHQ Hospital while 3.08% use the different modalities. 39.95% were bitten by Eristicophis, 10.97% Cobra, and 30.95% by viper and 18.13% Krait. Lower limb was the most frequent site of the snake bite (70.03%).Conclusion: Snake bite is one of a important problem in this district. We also concluded that Anti-snake venom shows better result and early treatment after snake bite can reduce the mortality rate